IN-SITU CO2 CURRENT EFFICIENCY MEASUREMENT OF DIRECT ETHANOL FUEL CELL - hariyanto, hariyanto (185P -3466)
In this present work, we carry out systematically study on catalyst for ethanol electrooxidation in direct ethanol fuel cell. For cathode catalyst we use a commercial catalyst of 40% Pt/C from ETEK. Catalysts were printed on to carbon paper of TGPH 060 and sandwiched into membrane electrode assembly (MEA) and then arranged in fuel cell with the geometric area 1.2 cm2. As an electrolyte, we used Nafion 117 from Du Pont. On-line Differential Electrochemical Mass Spectrometry (DEMS) measurement in fuel cell setup was carried out in order to determine the activity and selectivity which was indicated by result of Faradaic current and CO2 current efficiency of ethanol electro-oxidation respectively. PtRhCeO2/C was significantly improve the selectivity to form of CO2 in comparison to the commercial catalyst of 20% Pt/C from Alfa Aesar- Johnson Mattews . Increasing of selectivity is shown by increase of CO2 current efficiency of ethanol oxidation of about 25 percent in comparison to references catalyst of 20% Pt/C Alfa Aesar-JM